Effect of Retail Sales Promotion on Buying Behaviour of Customers: An Empirical Study - Das, Gopal (Indian Journal of Marketing, 2011)
The Indian market is currently witnessing a retail boom with Organized Retailers offering a whole assortment of goods and services to consumers under one roof with congenial shopping ambience. With the Indian retail boom, many players are entering the market with different retail formats. As a result, competition is becoming very tough. Each player is trying to attract more customers through different sales promotional activities. But, the exact picture of the impact of sales promotion on consumer behaviour is yet unclear to the retailers. This paper tries to find out the impact of demographic parameters on retail sales promotion and overall buyers' behavior on retail sales promotions.